Precision livestock farming for climate-resilient animal husbandry - Chandra, Vikash; Das, Pravasini; Singh, Gyanendra (Indian Farming, 2026)
Precision Livestock Farming (PLF) refers to the application of sensor-based technologies, automated monitoring systems, and data-driven analysis to manage livestock production efficiently. By enabling continuous monitoring of animal health, behaviour, and environmental conditions, PLF supports informed decision-making and enhances the resilience of livestock systems against the increasing challenges posed by climate change. PLF is intended to optimise livestock health, production, and welfare while addressing environmental challenges. Several PLF platforms have been developed, about estrus detection systems, calving detection, seasonal prediction of milk production, and seasonal health-related issues, as well as feeding regimens. The impacts of climate change, including rising temperatures, erratic precipitation patterns, and increased extreme weather events, demand adaptive strategies to ensure animal welfare.